Study on the Evaluation Methods of the Vertical Ride Comfort of Railway Vehicle—Mean Comfort Method and Sperling’s Method - Mădălina Dumitriu; Dragoș Ionuț Stănică (Applied Sciences, 2021)
The paper herein analyzes the ride comfort at the vertical vibrations of the railway vehicle, evaluated by two methods—mean comfort method and Sperling’s method. The two methods have in common that the estimation of the comfort sensation is conducted with the comfort indices, namely ride comfort index NMVZ and ride comfort index Wz. The values of these indices are derived from numerical simulations. The advantage of using the results of the numerical simulations versus using experimental results, on which most previous research is based, resides in the fact that the ride comfort indices can be examined while taking into account the influence of velocity and certain parameters altering the behavior of vertical vibrations of the carbody, i.e., carbody flexibility and the suspension damping. The numerical simulation applications have been developed based on a theoretical model of the vehicle that considers important factors affecting the behavior of vertical vibrations of the carbody, by means of a ‘flexible carbody’ type model and an original model of the secondary suspension. The results presented mainly show that the two assessment methods lead to significantly different outcomes, in terms of ride comfort, under identical running conditions of the vehicle.